Effects of CO2 enrichment on the anaerobic digestion of sewage sludge in continuously operated fermenters. (July 2021) - Muntau, Meriam; Lebuhn, Michael; Polag, Daniela; Bajón-Fernández, Yadira; Koch, Konrad
Graphical abstract: Highlights: Long-term continuous anaerobic digestion experiments treating sewage sludge (> 450 d). Effects of CO2 enrichment on the anaerobic digestion process. Significantly increased methane production as immediate response to CO2 enrichment. Sustainably enhanced specific methane production at higher organic loading rates. Improved process resilience after disturbance in a CO2 -enriched environment. Abstract: The effect of CO2 enrichment in sewage sludge anaerobic digestion (AD) as a potential strategy to improve the biogas yield was assessed at increasing organic loading rates (OLR). Effects on process performance and resilience were evaluated in long-term continuous AD experiments at lab-scale. The specific methane production (SMP) was sustainably enhanced in the test digester compared to a control at elevated OLRs, reaching an increase of 6 ± 12% on average at the highest OLR tested (4.0 kgVS /(m 3 ·d)). The reduction of CO2 via homoacetogenesis, facilitating acetoclastic CH4 formation is proposed as the dominant conversion pathway. Results suggest that sufficient load of easily degradable substances is a prerequisite for intrinsic formation of the reduction equivalent H2 via acidogenesis. The enhanced resilience of the process under CO2 -enriched conditions in response to acid accumulation further qualifies this approach as a viable option for improving AD performance by converting a waste stream into a valuable product.